2018
DOI: 10.1016/j.gene.2018.03.099
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptomic analysis to identify differentially expressed genes during the process of aerenchyma formation in Typha angustifolia leaves

Abstract: Lysigenous aerenchyma is formed through programmed cell death (PCD) in Typha angustifolia leaves. However, the genome and transcriptome data for this species are unknown. To further elucidate the molecular basis of PCD during aerenchyma formation in T. angustifolia leaves, transcriptomic analysis of T. angustifolia leaves was performed using Illumina sequencing technology, revealing 73,821 unigenes that were produced by assembly of the reads in T1, T2 and T3 samples. The important pathways, such as programmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Differential expression analysis of the three stages in MF and HF was performed using DESeq [116]. DESeq2 v1.4.5 was used for differential gene expression analysis, and a p -value could be assigned to each gene and adjusted by Benjamini and Hochberg’s approach for controlling the false discovery rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential expression analysis of the three stages in MF and HF was performed using DESeq [116]. DESeq2 v1.4.5 was used for differential gene expression analysis, and a p -value could be assigned to each gene and adjusted by Benjamini and Hochberg’s approach for controlling the false discovery rate.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences were designed using Primer premier 5.0, and Primer sequences and β - actin (as an internal control to normalize the expression levels of genes) sequence of internal reference gene are listed in Additional file 1. RNA was extracted from T. sinensis of three developmental stages, and RNA extraction, cDNA synthesis, and Real-time PCR method as described in related references [116, 123].…”
Section: Methodsmentioning
confidence: 99%
“…Since the WL-S accession revealed up-regulation of this gene after the second treatment (2xH), it could suggest that waterlogging acted as a priming factor in acquiring tolerance to waterlogging stress in the WL-S accession. Calmodulin-like proteins (CMLs) are sensors of Ca 2+ and take part in calcium signaling [68]. It has been reported that CMLs may be involved in aerenchyma formation, allowing plants to perform gas exchange between roots and shoots [69].…”
Section: Effects Of Waterlogging Stress Priming On the Wl-t And Wl-s Cucumber Accessionsmentioning
confidence: 99%
“…RNA-Seq analysis of separated embryonal mass and suspensor cells of Picea abies has shown that a spruce homolog of bax inhibitor-1 transcript is upregulated in early PCD suspensor cells and plays a role in regulating vacuolar cell death in suspensor cells [ 19 ]. Moreover, RNA-Seq analysis of early and late cavern forming leaf aerenchyma cells of Typha angustifolia revealed expansins, calmodulin-like proteins and pectinases transcripts that were directly related to lysigenous aerenchyma induction [ 20 ].…”
Section: Introductionmentioning
confidence: 99%